PENGARUH KOMPENSASI, LINGKUNGAN KERJA DAN PENGEMBANGAN KARIR TERHADAP TURNOVER INTENTION PADA KARYAWAN PT. KARYA SAWITINDO MAS - Novita Deska Putri; Islamuddin Islamuddin (Yayasan Insani Mandiri Santani, 2022)
The general objective of this research is to find out whether there is an effect of compensation, work environment and career development on turnover intention of Pt employees. The work of Sawitindo Mas. This research is an associative type of research, namely research that explains the influence between the independent variable and the dependent variable. This study uses a quantitative approach, namely a research method that emphasizes objective phenomena. The population in this study were all employees of PT. Karya Sawitindo Mas has 98 employees. Based on the results of multiple linear regression, the regression equation form Y = -0.365 - 0.681 (X1) - 0.278 (X2) - 0.316 (X3). The results of the Regression Coefficient X_1, of -0.681 have meaning if the value of the Compensation variable (X1) increases by one unit then The Turnover Intention (Y) value will increase by -0.681 assuming the Compensation variable (X1) is considered constant. The Regression Coefficient X2, which is -0.278 means that if the value of the Work Environment (X2) variable increases by one unit, the Turnover Intention (Y) value will increase. of -0.278 with the assumption that the Work Environment variable (X2) is considered constant. The Regression Coefficient of X3, of -0.316 means that if the value of the Career Development variable (X3) increases by one unit, the Turnover Intention (Y) value will increase by -0.316 assuming the Factor variable Career Development (X3) is considered fixed. Conclusion Compensation has a negative and significant effect on Turnover Intention at PT. The work of Sawitindo Mas, this is evidenced by the results of the t test showing that the results of the study are t_hit>t_(Î±/2) (-7,570 > 1,985) and (sig = 0.000 < 0.050). Work Environment has a negative and significant effect on Turnover Intention at PT. The work of Sawitindo Mas, this is evidenced by the results of the t-test showing that the results of the study are t_hit>t_(Î±/2) (-6.347>1.985) and (sig = 0.000 < 0.050). Career Development has a negative and significant effect on Turnover Intention at PT. The work of Sawitindo Mas, this is evidenced by the results of the t test showing that the results of the study are t_hit>t_(Î±/2) (-3.147 >1.985) and (sig = 0.002 < 0.050).Â Â Keywords: Compensation, Work Environment, Career Development, Turnover Intention